2011
DOI: 10.1186/cc10200
|View full text |Cite|
|
Sign up to set email alerts
|

C-reactive protein/albumin ratio at ICU discharge as a predictor of post-ICU death: a new useful tool

Abstract: Introduction Noninvasive ventilation is a safe and eff ective method to treat acute respiratory failure, minimizing the respiratory workload and oxygenation. Few studies compare the effi cacy of diff erent types of noninvasive ventilation interfaces and their adaptation. Objective To identify the most frequently noninvasive ventilation interfaces used and eventual problems related to their adaptation in critically ill patients. Methods We conducted an observational study, with patients older than 18 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Similarly in our study, we found that as the level of CRP increases in patients of COPD with acute exacerbation the prognosis became poor and we found that chances of poor outcome are high when a patient will presents with initial CRP values of more than or equal to 17.5 mg/dL. [17] Azevedo et al [18] conducted a study to find the correlation of ratio of CRP/ albumin in patients of COPD hospitalized in ICU with the prognosis of the patient. They found that higher the ratio, poorer the outcome of the patient.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly in our study, we found that as the level of CRP increases in patients of COPD with acute exacerbation the prognosis became poor and we found that chances of poor outcome are high when a patient will presents with initial CRP values of more than or equal to 17.5 mg/dL. [17] Azevedo et al [18] conducted a study to find the correlation of ratio of CRP/ albumin in patients of COPD hospitalized in ICU with the prognosis of the patient. They found that higher the ratio, poorer the outcome of the patient.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, we found that initial CRP levels in patients of COPD can predict admission in ICU/ ward and we concluded that any patient of COPD coming with acute exacerbation with CRP levels equal to or more than 11.2 mg/dL needs admission in ICU. [18] The strength of this study is that CRP is a single, cheap, easily available systemic inflammatory marker, which can guide us regarding prognosis in COPD, pneumonia, asthma, and ARDS and its values correlate with improvement and poor outcome. As positive correlation was found between CRP value and admission in ICU, therefore CRP can guide us about the site of management.…”
Section: Discussionmentioning
confidence: 98%
“…After the publication of this abstract [ 1 ], we found that not all data of results section were published. The complete multivariate analysis and the best cut-off value of the CRP/albumin ratio are now published: The multivariate analysis resulted in the follow independent in-hospital death predictors: Age (OR 1.028, 95% CI 1.014-1.043, p = 0< 0.001), comorbitidies (OR 1.247, 95% CI 1.036-1.500, p = 0.020), ICU LOS (OR 1.031, 95% CI 1.003-1.0609, p = 0.029), Septic Syndrome (OR 1.683, 95% CI 1.027-2.758, p = 0.039), SOFA (OR 1.284, 95% CI 1.151-1.432, p < 0.001) and CRP/albumin ratio (OR 1.809, 95% CI 1.099-2.977, p = 0.020).…”
Section: Correctionmentioning
confidence: 99%